Optimalisasi Peran Kader PIK-R: Transformasi Pengetahuan TRIAD KRR melalui Program Edukasi Kesehatan - Sheilia Handi Dwi Fadellia Maharani Putri; Nur Azizah Indriastuti (Pustaka Galeri Mandiri, 2026)
The three critical risk factors for adolescent reproductive health (TRIAD KRR) is an important issue that requires more attention. PIK-R staff are agents of change and act as partners who can influence young people themselves. Therefore, there is a need to improve staff knowledge about the TRIAD KRR by providing reproductive health education as a key strategy in efforts to improve PIK-R staff knowledge about the TRIAD KRR. This study aims to analyze the impact of health education on the knowledge level of PIK-R program staff about this triad. The study used a quasi-experimental design with a single group and pre- and post-tests. The sample consisted of 15 PIK-R program staff selected using a large-scale sampling method. The statistical analysis in this study was based on the Wilcoxon Signed-Rank test. The results showed a statistically significant difference in the knowledge level of the participants before receiving the health education program, with 10 participants (66.7%) having a good level of knowledge and 5 participants (33.3%) having a sufficient level of knowledge. After the program, 12 participants (80%) demonstrated a good level of knowledge, while 3 participants (20%) demonstrated a sufficient level of knowledge. Statistical analyses showed a statistically significant difference (p = 0.001, p < 0.05) between the level of knowledge before and after the health education program on the KRR TRIAD model. Therefore, it can be assumed that the health education had a significant impact on the knowledge of the participants in the PIK-R program on the TRIAD KRR model